Analysis of the Progress in Identification and Evaluation of Laboratory Animal Resources in China - DU Xiaoyan; LIU Yunbo (Shiyan dongwu yu bijiao yixue)
Laboratory animals are not only a national strategic resource but also an important support for development of science and technology. The Committee of Identification and Evaluation for Laboratory Animal Resources, organized by Chinese Association for Laboratory Animal Sciences and established in May 2019, is currently the only specialized academic agency dedicated to the identification and evaluation of laboratory animal resources in China. This paper first discusses the significance of identifying and evaluating laboratory animal resources, summarizes three new approaches to developing these resources, including the domestication and standardization of laboratory animals (economic, ornamental, agricultural, and wild animals, etc.), the acquisition of new strains (species) through natural mutation and induced mutation, and the creation of new laboratory animal resources through gene editing technology. It then introduces the workflow for resource identification and evaluation, including preliminary review (format review), written review (expert review), joint review or on-site inspection, final review (voting and public announcement)，and the issuance of certificates. The required materials to be submitted include application, summary report, research or identification reports, appendices and other necessary documents. The paper further discusses related requirements for resource identification and evaluation, including population, genetic classification, biological characteristics, genetic stability, and application value. Finally, the current status of newly identified laboratory animal strains (species) and issues in current work practices are analyzed, as well as solutions to these issues. This paper aims to provide a valuable reference for further research in this field.